Optimal timing of salvage radiotherapy for biochemical recurrence after radical prostatectomy: is ultra-early salvage radiotherapy beneficial?. Issue 1 (December 2016) - Taguchi, Satoru; Shiraishi, Kenshiro; Fukuhara, Hiroshi; Nakagawa, Keiichi; Morikawa, Teppei; Naito, Akihiro; Kakutani, Shigenori; Takeshima, Yuta; Miyazaki, Hideyo; Nakagawa, Tohru; Fujimura, Tetsuya; Kume, Haruki; et al.
Abstract Background The optimal timing of salvage radiotherapy for biochemical recurrence after radical prostatectomy is controversial. In particular, the prognostic significance of salvage radiotherapy delivered before a current definition of biochemical recurrence, i.e. ultra-early salvage radiotherapy, is unclear. Methods We reviewed 76 patients with pT2-3N0M0 prostate cancer who underwent salvage radiotherapy for post-prostatectomy biochemical recurrence at the following three timings: ultra-early salvage radiotherapy (n  = 20) delivered before meeting a current definition of biochemical recurrence (two consecutive prostate-specific antigen [PSA] values ≥0.2 ng/mL); early salvage radiotherapy (n  = 40) delivered after meeting the definition but before PSA reached 0.5 ng/mL; and delayed salvage radiotherapy (n  = 16) delivered after PSA reached 0.5 ng/mL. The primary endpoint was failure of salvage radiotherapy, defined as a PSA value ≥0.2 ng/mL. The log-rank test and Cox proportional hazards model were used for univariate and multivariate analyses, respectively. Results During the follow-up period (median: 70 months), four of 20 (20 %), nine of 40 (23 %) and seven of 16 (44 %) patients failed biochemically in the ultra-early, early and delayed salvage radiotherapy groups, respectively. On univariate analyses, the outcome of delayed salvage radiotherapy was worse than the others, while there was no significant difference between ultra-early and early groups. Multivariate analysis demonstrated the presence of Gleason pattern 5, perineural invasion and delayed salvage radiotherapy as independent predictors of poorer survival. Conclusions No survival benefit of ultra-early salvage radiotherapy was demonstrated, whereas delayed salvage radiotherapy was associated with worse outcome as reported in previous studies. Our results may support the current recommendations that salvage radiotherapy should be undertaken after two consecutive PSA values ≥0.2 ng/mL and before reaching 0.5 ng/mL.